Analysis of Trans Fatty Acid Content and Viscosity of the Repeteadly Used Frying Oil - Andi Abriana; Meta Mahendradatta; Natsir Djide; Zainal Zainal (International Journal of Agriculture System, 2013)
The physicochemical properties of the repeatedly used frying oil were subjected to changes at frying temperature of 180oC and frying time of 10 minutes with five times frying repetitions. The changes included the formation of trans fatty acids and increased viscosity. The trans fatty acid content was analyzed by gas chromatography (GC) and the viscosity by “Brookfield DV-E Viscometer”. The trans fatty acid content and the viscosity of the repeatedly used frying oil increased with the number of repeated uses and the trans fatty acid content increased with the viscosity. The higher the trans fatty acid, the higher the viscosity of the frying oil. The increased trans fatty acid content and viscosity indicated that a damage had occurred in the oil.